2010
DOI: 10.4062/biomolther.2010.18.4.469
|View full text |Cite
|
Sign up to set email alerts
|

The Promotive Effects of Antioxidative Apigenin on the Bioavailability of Paclitaxel for Oral Delivery in Rats

Abstract: -This study was to investigate the effect of apigenin on the bioavailability of paclitaxel after oral and intravenous administration in rats. The effect of apigenin on P-glycoprotein (P-gp), cytochrome P450 (CYP)3A4 activity was evaluated. The pharmacokinetic parameters of paclitaxel were determined in rats after oral (40 mg/kg) or intravenous (5 mg/kg) administration of paclitaxel with apigenin (0.4, 2 and 8 mg/kg) to rats. Apigenin inhibited CYP3A4 activity with 50% inhibition concentration (IC50) of 1.8 μM.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…[22] Apigenin has been shown to inhibit P450 3A4 in an assay using 7-benzyloxy-4-trifluoromethylcoumarin as the marker substrate with an IC50 value of 1.8 µM. [23] Another group obtained an IC50 value of 31 ± 8 µM for apigenin using 7-benzyloxymethyloxy-3-cyanocoumarin as the marker substrate of cytochrome P450 3A4. [24] Use of different substrates for determining cytochrome P450 3A4 enzyme activity can explain observed differences in IC50 values between studies.…”
Section: Results and Discusionmentioning
confidence: 99%
“…[22] Apigenin has been shown to inhibit P450 3A4 in an assay using 7-benzyloxy-4-trifluoromethylcoumarin as the marker substrate with an IC50 value of 1.8 µM. [23] Another group obtained an IC50 value of 31 ± 8 µM for apigenin using 7-benzyloxymethyloxy-3-cyanocoumarin as the marker substrate of cytochrome P450 3A4. [24] Use of different substrates for determining cytochrome P450 3A4 enzyme activity can explain observed differences in IC50 values between studies.…”
Section: Results and Discusionmentioning
confidence: 99%
“…18) In addition, apigenin has demonstrated anticonvulsant effects in picrotoxin-induced rats. 20) Despite the widespread use of apigenin, 21) knowledge of its mechanism of action or protective effects on glutamate-mediated toxicity is limited. In this study, to elucidate these issues, we investigated the protective effects and possible mechanism of apigenin induced by excitotoxicity in hippocampal neurons.…”
mentioning
confidence: 99%
“…To improve the efficiency of oral delivery of PTX, some investigations have been performed by the suppression of ABCB1 and metabolic enzymes. PTX is a substrate of ABCB1 and several studies have reported that its oral bioavailability was substantially increased by PTX coadministration with ABCB1 inhibitors [114]. As formerly mentioned, apigenin sensitized prostate [101], uterine [103], and breast [104] cancer cells to DOX by ABCB1 inhibition.…”
Section: Paclitaxelmentioning
confidence: 99%
“…Apigenin also significantly increased the terminal half-life of PTX when it was used orally. Taken together, the improvement of oral bioavailability of PTX by apigenin might be due to enhanced intestinal absorption owing to ABCB1 inhibition by apigenin [114,115]. Xu et al showed that apigenin could sensitize different human cancer cells such as cervical epithelial carcinoma, lung epithelial carcinoma, and hepatocyte carcinoma cells to PTX through inducing apoptosis by suppressing SOD activity leading to accumulation of ROS and caspase-2 cleavage [116].…”
Section: Paclitaxelmentioning
confidence: 99%